Dreamland's: know about science light and colour - Talwar, L.M (Dreamland Publications New Delhi, 1995)
Dreamland's: Know About Science - Light and Colour explores the fundamental concepts of light and color, introducing young readers to topics like how light travels, the properties of different colors, and phenomena such as rainbows. Through engaging illustrations and simple explanations, the book encourages curiosity and hands-on exploration, making science accessible and fun.